2009
DOI: 10.1177/0091270008330980
|View full text |Cite
|
Sign up to set email alerts
|

The Targeted Oral, Once‐Daily Phosphodiesterase 4 Inhibitor Roflumilast and the Leukotriene Receptor Antagonist Montelukast Do Not Exhibit Significant Pharmacokinetic Interactions

Abstract: This nonrandomized, fixed-sequence, 3-period study investigated potential pharmacokinetic interactions between the leukotriene receptor antagonist montelukast, approved for the treatment of asthma, and roflumilast, an oral, once-daily phosphodiesterase 4 inhibitor in clinical development for asthma and chronic obstructive pulmonary disease. Pharmacokinetic interactions are of interest because both drugs may be coadministered and share a common metabolic pathway via cytochrome P450 3A. Single-dose montelukast (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The contribution of the N-oxide metabolite was modeled to be greater than the parent, and interestingly, based on comparisons of healthy volunteers and COPD patients, this contribution was modeled to be even greater in the patients. Using exposure values from Böhmer et al, (2009) Sibutramine offers an interesting example of two active metabolites and an instance wherein the parent drug probably contributes little effect. It was used as a weight-loss agent, although safety problems led to its removal from clinical practice.…”
Section: Procainamidementioning
confidence: 99%
“…The contribution of the N-oxide metabolite was modeled to be greater than the parent, and interestingly, based on comparisons of healthy volunteers and COPD patients, this contribution was modeled to be even greater in the patients. Using exposure values from Böhmer et al, (2009) Sibutramine offers an interesting example of two active metabolites and an instance wherein the parent drug probably contributes little effect. It was used as a weight-loss agent, although safety problems led to its removal from clinical practice.…”
Section: Procainamidementioning
confidence: 99%
“…Neither roflumilast nor roflumilast N-oxide by themselves inhibit CYP3A4 or CYP1A2 (40). Other data suggest a low potential for roflumilast to interact adversely with other drugs including montelukast, erythromycin, ketoconazole, budesonide, albuterol, midazolam (40), and antacids containing magnesium hydroxide or aluminium hydroxide (59)(60)(61)(63)(64)(65)(66)(67). This is important to determine because inducers of CYP3A4 and CYP1A2 have the potential to increase the CL of roflumilast thereby lowering its efficacy.…”
Section: Contraindications Effect Of Food and Drug-drug Interactionsmentioning
confidence: 99%
“…Correspondingly, agents that are metabolized by the same system could compete with roflumilast and delay its inactivation, in effect raising its level. A number of studies have been performed to evaluate such drug-drug interactions and their potential for adverse reactions (59)(60)(61)(62)(63)(64)(65)(66)(67). The results published so far indicate that there is not a substantial effect of a range of potential agents and conditions on roflumilast levels.…”
Section: Safety Outcomesmentioning
confidence: 99%
“…B€ ohmer et al 27 reported that the pharmacokinetics of roflumilast and roflumilast N-oxide (its active metabolite) in steady state remain unchanged when montelukast is coadministered at steady state and that both drugs are well tolerated. Thus no dose adjustment for either drug is necessary when roflumilast and montelukast are coadministered.…”
Section: Discussionmentioning
confidence: 99%